2022
DOI: 10.21203/rs.3.rs-2216232/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meiotic abnormalities in sugarcane (Saccharum spp.): Evidence for peri- and paracentric inversions

Abstract: The modern cultivars of sugarcane (Saccharum spp.) are highly polyploid and accumulate aneuploidies due to their history of domestication, genetic improvement and interspecific hybrid origin involving the domesticated sweet species S. officinarum ('noble cane') and the wild S. spontaneum, both with an evolutionary history of polyploidy. The first hybrids were backcrossed with S. officinarum, and selection from progenies in subsequent generations established the genetic basis of modern cultivars. Saccharum geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…It is an establishing autopolyploid (Van Drunen & Friedman, 2022), with several cytotypes and basic chromosome numbers ( x ) equal to 10, 9, and 8 (Piperidis & D'Hont, 2020), being x = 8 the most common. Its meiosis is irregular with approximately 52% of cells exhibiting abnormalities and up to two univalent are seen in diakinesis (Oliveira et al., 2023). Therefore, it is reasonable to speculate that meiotic cells require a higher expression of ZIP4 for regulation of meiotic synapsis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is an establishing autopolyploid (Van Drunen & Friedman, 2022), with several cytotypes and basic chromosome numbers ( x ) equal to 10, 9, and 8 (Piperidis & D'Hont, 2020), being x = 8 the most common. Its meiosis is irregular with approximately 52% of cells exhibiting abnormalities and up to two univalent are seen in diakinesis (Oliveira et al., 2023). Therefore, it is reasonable to speculate that meiotic cells require a higher expression of ZIP4 for regulation of meiotic synapsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, using genomic in situ hybridization (GISH), we also determined the origin of lagging chromosomes, mostly from S. spontaneum and from interspecific recombination events, suggesting that there is coordinated, non‐random meiotic chromosome segregation. In all, our previous studies revealed the existence of mechanisms that regulate meiosis, and they require further in‐depth investigation (Oliveira et al., 2023; Vieira et al., 2018).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The two latter exhibited several abnormalities, including delayed chromosomes, from metaphase I to the end of the division, while the S. officinarum clone showed regular behavior. In this study, we visualized the presence of dicentric chromosomes, and a pericentric inversion that was particularly evidenced by a detailed pachytene analysis (Oliveira et al 2022).…”
Section: Introductionmentioning
confidence: 99%